Examination of Students' Social Entrepreneurial an Observational Test - Zainab Y. Alsheikhly; Raz A. Jalal; Qusay H. Al-Salami (Cihan University-Erbil Journal of Humanities and Social Sciences)
This paper examines the disparity between male and female Syrian university students in enhancing intellectual awareness and developing entrepreneurial skills in the charitable sector. It explores how these influential groups can contribute to activating the roles of institutions and individuals in serving society humanely. The study's hypotheses were based on variables such as entrepreneurial intentions, self-efficacy, perceived social support, moral obligation, and empathy. Results support the existence of gender differences among private university students. Findings reveal that many Syrians have the potential and strong desire to become social entrepreneurs despite facing significant economic and social challenges. The study also underscores the urgent need for systematic education for those addressing social issues in Syria. It recommends that Syrian educational institutions incorporate courses on social entrepreneurship, possibly through relevant elective courses.